The Neuroprotection of KIBRA in Promoting Neuron Survival and Against Amyloid β-Induced Apoptosis - Song, Lin; Tang, Shi; Dong, Lingling; Han, Xiaolei; Cong, Lin; Dong, Jixin; Han, Xiaojuan; Zhang, Qinghua; Wang, Yongxiang; Du, Yifeng (Frontiers in Cellular Neuroscience, 2019)
Background: Recent research has identified the nucleotide polymorphisms of KIBRA to be associated with cognitive performance, suggesting its vital role in Alzheimer’s disease (AD); however, the underlying molecular mechanism of KIBRA in AD remains obscure. Methods: The AD animal model (APP/PS1 transgenic mice) and KIBRA knockout (KIBRA KO) mice were used to investigate pathophysiological changes of KIBRA in vivo. Mouse hippocampal cell line (HT22) was used to explore its molecular mechanism through KIBRA CRISPR/Cas9-sgRNA system and KIBRA overexpression lentivirus in vitro. Results: Aged APP/PS1 mice displayed increased neuronal apoptosis in the hippocampus, as did KIBRA KO mice. KIBRA deficiency was closely related to neuronal loss in the brain. In addition, knockdown of KIBRA in neuronal cell lines suppressed its growth and elevated apoptosis-associated protein levels under the stress of Aβ1-42 oligomers. On the contrary, overexpression of KIBRA significantly promoted cell proliferation and reduced its apoptosis. Moreover, through screening several survival-related signaling pathways, we found that KIBRA inhibited apoptosis by activating the Akt pathway other than ERK or PKC pathways, which was further confirmed by Akt-specific inhibitor MK2206. Conclusion: Our data indicate that KIBRA may function as a neuroprotective gene in promoting neuron survival and inhibiting Aβ-induced neuronal apoptosis.